HIDUP HARMONIS: KAWASAN WISATA ALAM SEBAGAI MEDIA PEMBELAJARAN PENGALAMAN BUDAYA SUNDA - Wandi Krisdian; Asep Yudi Permana; Mokhammad Syaom Barliana (KBK Peracangan Arsitektur dan Kota Program Studi Arsitektur Fakultas Pendidikan Teknologi, 2022)
Abstract: In their culture, Sundanese people recognize the concept of 3 certainty of life as a philosophy of life, which is known as